Press release of the Baltimore and Ohio Railroad Company - Stevens, Margaret Talbott, 1892-1955.
Press release, written by Stevens, noting the centennial anniversary of the arrival of the first locomotive train in Washington, D.C., from Baltimore, Md., on August 24, 1835.
Typewritten transcript.
Editor and librarian, Baltimore and Ohio Railroad.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baltimore and Ohio Railroad Company; Railroads -- Anniversaries, etc; Railroads -- Maryland -- Baltimore; Railroads -- Washington (D.C.); Editors; Librarians